Penerapan Metode Perbandingan Eksponensial (MPE) Dalam Menentukan Topik Skripsi, Dosen Pembimbing Beserta Dosen Pembanding Studi Kasus Fakultas Ilmu Komputer Universitas Methodist Indonesia - Gideon Haloho Haloho; Samuel Manurung; Naikson Fandier Saragih (Department of Information Technology, Universitas Timor, Indonesia, 2022)
The research that the author made discusses the application of the exponential comparison method (MPE) in determining thesis topics, supervisors and comparative lecturers of case studies at the Faculty of Computer Science, Indonesian Methodist University which aims to produce decisions in the selection of thesis topics, supervisors and comparison lecturers according to the criteria in Indonesian Methodist University. A decision support system (SPK) is needed that can find the student title value from each criterion that has been determined by the Indonesian Methodist University for the decision-making process. Applying the Exponential Comparison Method (MPE) using the criteria that have been determined by the campus, namely being registered as active students, having completed a minimum of 100 credits, students conducting research and compiling thesis manuscripts. The decision support system for selecting topic titles, supervisors and comparison lecturers made by the author uses the PHP programming language, and uses a MySQL database that is run on the Windows operating system